'If they'd written more…' – On students' perceptions of assessment and assessment practices. Issue 2 (1st January 2016) - Torkildsen, Lisbeth Gyllander; Erickson, Gudrun
Abstract : The focus of the current study is students' perceptions of assessment and assessment practices. Assessment is understood as practices closely connected to the planning, enactment and evaluation of teaching and learning activities. The data derive from focus group interviews and dialogical meetings with students at a Swedish comprehensive school. Theories of assessment and validity are used as a framework to interpret and contextualise the data. An empirically developed interconnecting data analysis model is used as an analytical tool to connect students' perceptions, assessment aspects and preconditions in a specific context. Our results indicate that students perceive assessment at different comprehension levels, categorised as performing, understanding and learning. Preconditions affect students' possibilities of accessing assessment practices and using assessments to improve their performance. In this article we highlight the importance of taking student voice and preconditions into consideration when structuring accessible and meaning-making assessment practices that hold possibilities for enhanced learning.